Determinants of Students’ Green Waqf Intentions - Taufik, Nisrina Amani; Shofawati, Atina (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
Green Waqf is the use of waqf assets to support environmental sustainability and provide social and economic benefits. Its success depends on the intention of the community, including students who have high concern for environmental issues. This research analyzes the factors that influence the intentions of Islamic Economics students at Airlangga University to give green waqf, with the variables Attitude, Subjective Norms and Perceived Behavioral Control. Attitudes are influenced by Knowledge and Religiosity. This research uses a quantitative approach with PLS-SEM analysis. Data was obtained from questionnaires distributed to 145 respondents, with a final sample of 127 students. The research results show that Knowledge and Religiosity have a significant positive effect on Attitude. Subjective Norms and Perceived Behavioral Control also have a significant positive effect on Green Waqf Intentions, while Attitude has no significant effect. Therefore, strategies are needed to increase students' intention to engage in green waqf, such as education through social media by involving figures or influencers, as well as encouraging student participation in green waqf activities.